Research on Cognitive Bias in Online Public Opinion - Chen, Jingqi (International Journal of Computer Science and Information Technology, 2024)
In the era of big data, there is a tremendous amount of information on the Internet, but people can only access part of it. Information obtained through only limited channels can easily cause cognitive bias and expand the influence of related online public opinions. This article explores the origins of bias, from the overwhelming influx of information to the personalized recommendation algorithms and homogeneity within social media groups. To combat these issues, the paper proposes solutions such as data preprocessing techniques, information dissemination methods, and measures to ensure algorithmic fairness. Beyond this, truly solving the problem requires interdisciplinary collaboration and multi-stakeholder engagement to effectively address these challenges, emphasizing efforts in public education, platform governance, and regulatory frameworks.